Development of Harmoni Nusantara Website Based on Problem Based Learning to Improve Critical Thinking Skills of Students of SMAN 9 Malang - Valeria, Aurel Hamida; Sukriono, Didik; Hadi, Nuruddin (Electronic Journal of Education, Social Economics and Technology, 2024)
This study aims to develop and test the effectiveness of website-based learning media Harmoni Nusantara with a Problem-Based Learning (PBL) approach in improving critical thinking skills of students at SMAN 9 Malang. The study uses the Research and Development (RD) development method with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model. This model was chosen because the process is systematic, structured, and provides evaluation at each stage of development, making it suitable for producing valid and effective learning media products, both for online and offline learning. The development process involved interviews with PPKn teachers for needs analysis, as well as validation by media experts, material experts, and students. Data collection was carried out through product validation questionnaires and formative tests (pretest and posttest). Data analysis used a quantitative approach with a Likert scale for media validation, as well as normality, homogeneity, and t-test tests for the effectiveness of learning outcomes. The Harmoni Nusantara website is designed with interactive features such as learning materials, educational videos, quizzes, and educational games. The results of the effectiveness test showed a significant increase in students' critical thinking skills after using this media. The normality test showed that the data was normally distributed (pretest significance 0.251 and posttest 0.170), the homogeneity test showed homogeneous data (significance 0.124), and the t-test showed a significant value (0.00 0.05) with a t-count value of -10.785. This proves that the Harmoni Nusantara website-based learning media is effective in improving students' critical thinking skills.